Effects of Basic Psychological Needs Satisfaction in the Physical Education on Leisure-Time Physical Activity Behavior of Primary School Students: Mediating Role of Autonomous Motivation - MehdiGholi Gholidahaneh; Saeed Ghorbani; Akram Esfahaninia (Shiraz University of Medical Sciences, 2020)
Background: Recognizing the factors influencing students' participation in leisure-time physical activity is considered as an important topic concerning school health. The present study aimed to investigate the effects of basic psychological needs satisfaction in physical education (PE) classes on leisure-time physical activity behavior of primary school students, considering the role of autonomous motivation as a mediator variable. We further examined gender differences. Methods: We made use of a descriptive-correlation approach in the present study, 2019. Participants comprised 516 primary school students from Gonbad Kavoos. Research instruments included Sport Climate Questionnaire, Sport Motivation Scale, and Leisure-Time Physical Activity Behavior Scale. To analyze the data, we used the structural equation method and Mann-Whitney U test. Results: The results of structural equation method showed significant relationships between basic psychological needs satisfaction and leisure-time physical activity and autonomous motivation (all T>1.96). Furthermore, autonomous motivation had a positive association with leisure-time physical activity (all T>1.96), and it mediated the relationships between basic psychological needs satisfaction and leisure-time physical activity (all P<0.001). In addition, compared with girls, boys reported significantly higher satisfaction regarding competence and relatedness needs (P=0.040, P=0.009, respectively), higher intrinsic motivation and identified regulation (P<0.001, P=0.001, respectively), and higher leisure-time physical activity (P=0.045). Conclusions: Basic psychological needs satisfaction in PE classes positively influenced motivation and leisure-time physical activity in primary school children. Physical educators should encourage basic psychological needs satisfaction in students with regard to their activities in PE classes, in order to improve their participation in leisure-time physical activities